Comparative study of hydrogen and methane production in the human colon using caecal and faecal homogenates. Issue 6 (June 1990) - Flourié, B; Etanchaud, F; Florent, C; Pellier, P; Bouhnik, Y; Rambaud, J C
Abstract : Rates of hydrogen and methane production were compared in caecal and faecal homogenates in six methane producers. Faecal homogenates produced hydrogen and methane in the absence of and after the addition of lactulose, whereas caecal homogenates produced hydrogen but little methane.